Toward the Positive Consequences of Teacher-Student Rapport for Students' Academic Engagement in the Practical Instruction Classrooms - Zhou, Xiuqin (Frontiers in Psychology, 2021)
Due to the fact that teacher-student rapport may favorably influence students’ academic behaviors, several scholars have empirically studied the impact of this interpersonal communication behavior on a range of student-related variables. Notwithstanding, academic engagement as another student-related variable has received less empirical attention. Further, no review study has been carried out to illustrate the beneficial outcomes of teacher-student rapport for students’ involvement. The current study, hence, aims to fill these gaps by explaining the construct of teacher-student-rapport and its positive consequences for students’ academic engagement in the practical instruction classrooms. Drawing on the available evidence, the positive impact of teacher-student rapport on students’ academic engagement was illuminated. The significant implications of the finding are also discussed.